Control Strategies for solar façade panels coupled with a Heat Pump and interacting with a District Heating Network - Rattazzi D. (E3S Web of Conferences, 2019)
This work aims to understand the potential of an innovative technology for solar energy harvesting in a District Heating Network (DHN). The considered technology is aesthetic solar façade thermal panel. In order to guarantee the temperatures required by a 3rd generation DHN (around 75°C), a Heat Pump, using as cold source the heat from the panels, is necessary. It is worth noting that the coupling between façade panels and Heat Pump requires accurate evaluations. The optimum condition for the façade panels is to work at low temperatures (close to ambient or even below), while the Heat Pump reaches high Coefficient Of Performance (COP) when the temperature difference between hot and cold sources is minimized. In the first part of the study, a system model has been built using Matlab SIMULINK using results of tests on the panels already performed inside the H2020 ENVISION project. Different colours are considered. In the second part, a predictive mode-based strategy has been defined and tuned on the system in order to guarantee the best system performances in interaction with the DHN. This work will allow to understand whether this technology is feasible in the presented scenario and this layout can improve local energy exchange.